PHYSICAL CONDITIONS OF DOMESTIC ANIMALS DURING THE ROAD TRANSPORT - Dobrotkova, Marta (Doprava a spoje, 2009)
The amount of space allowed for an animal during transport is one of the most important factors influencing its welfare. Absolute minimum space allowances are determined by the physical dimensions of animals. The aim of this article was to show which factors determines physical condition